RAD51AP1 and RAD54L Can Underpin Two Distinct RAD51-Dependent Routes of DNA Damage Repair via Homologous Recombination - Selemenakis, Platon; Sharma, Neelam; Uhrig, Mollie E.; Katz, Jeffrey; Kwon, Youngho; Sung, Patrick; Wiese, Claudia (Frontiers in Cell and Developmental Biology, 2022)
Homologous recombination DNA repair (HR) is a complex DNA damage repair pathway and an attractive target of inhibition in anti-cancer therapy. To help guide the development of efficient HR inhibitors, it is critical to identify compensatory HR sub-pathways. In this study, we describe a novel synthetic interaction between RAD51AP1 and RAD54L, two structurally unrelated proteins that function downstream of the RAD51 recombinase in HR. We show that concomitant deletion of RAD51AP1 and RAD54L further sensitizes human cancer cell lines to treatment with olaparib, a Poly(adenosine 5´-diphosphate-ribose) polymerase inhibitor, to the DNA inter-strand crosslinking agent mitomycin C, and to hydroxyurea, which induces DNA replication stress. We also show that the RAD54L paralog RAD54B compensates for RAD54L deficiency, although, surprisingly, less extensively than RAD51AP1. These results, for the first time, delineate RAD51AP1- and RAD54L-dependent sub-pathways and will guide the development of inhibitors that target HR stimulators of strand invasion.